Urinary Detection of COVID-19 Virus and its Implication in Urology Practice (Sir Salimullah Medical College Journal, 2023)
Background: More than 25 crores of world population is affected by the pandemic corona virus SARS-CoV-2 since its first detection from Wuhan, china on December 2019. The widely accepted routes of human to human transmission for COVID-19 are through respiratory droplets and direct contact, however viral shedding in urine has been reported and infection transmission through infected urine remains a possibility.Objective of the study: To investigate the presence of COVID-19 virus in urine of infected patients and evaluate the probability of infection transmission through urine in different urological procedure.Methodology: After obtaining approval from institutional review board (IRB) of BSMMU this prospective cross-sectional observational study was conducted in the department of urology BSMMU from September 2020 to august 2021. Informed written consent was taken from the patients, the patients who are in ventilators legal guardian signed the consent form. After taking relevant history from the patients admitted in covid dedicated unit of BSMMU urine of the patients was collected in sterile container and with appropriate labeling and it was sent in virology department to detect the presence of SARS-COV-2 by quantitative real time polymerase chain reactions (RT-PCR). The date of covid 19 infection, date of urine sample collection, previous renal status, present renal function all were recorded.Results: Fifty patients were enrolled for investigation for detection of covid 19 virus in urine who were infected with SARS-COV-2. Thirty patients were male and Twenty were female. Male and female sex ratio was 3:2. We found the presence of SARS-COV-2 in urine of 2 patients, one male and one female. The rate of detection of SARS-COV-2 virus in urine of patients infected by covid 19 virus was 4%.Conclusion: Urinary detection of COVID-19 Virus was lower than oropharyngeal and rectal samples. Urological surgical intervention should be performed with caution considering the possibility of urine infection and possibility of COVID-19 transmission through this route.Sir Salimullah Med Coll J 2023; 31: 116-119